A claim to territory: hybrid solutions to securing land rights in the continuum between socially based and individualised tenure. Issue 375 (1st November 2020) - Goodwin, David
Abstract : Rights to land situated in the continuum between socially based (or communal) and individualised (or formal or western) tenure are often weak, and right holders may derive security both from traditional ceremonies and from mimicking elements of individualised tenure. This research investigates the way that entries Zimbabwe's development levy register – which was never intended as a title register – can help to secure land rights. A nuanced understanding is sought of issues involved in paying (or not paying) development levies at district and village level, and of how parts of the system are used by right holders as a first-stage cadastre capable of delivering a degree of land right security. GRAPHICAL ABSTRACT: